(untitled) (Physical Education, Health and Social Sciences, 2025)
Cardiac arrest is one of the major causes of death worldwide, and the pathogenesis of the condition lies within the background. Cardiovascular ailments including atherosclerosis, heart attack and malignant cardiac arrhythmias. Another key pathological mediator of these conditions is oxidative stress, the imbalance between the generation of reactive oxygen species (ROS) and the antioxidant defenses of the body. This narrative review is intended to summarize the existing evidence that the particular antioxidant-containing functional foods, i.e. berries, pomegranate and green tea are able to play a role in alleviating such oxidative load and also lower the risk of cardiac arrest. These foods contain the bioactive properties of anthocyanins, punicalagins and catechins, which have pleiotropic cardioprotective properties that cannot be limited to radical scavenging alone. These mechanisms can be the upregulation of endogenous antioxidant enzymes, enhancement of endothelial activity by guarding against nitric oxide bioavailability, systemic inflammation, and stabilized cardiac ion channels to avert arrhythmogenesis. Both pre-clinical models and human interventional studies have provided supporting evidences that regular intake of these foods can positively impact important risk factors such as hypertension, dyslipidemia and arterial stiffness. The incorporation of these nutritional elements into a heart-healthy dietary pattern holds promise and is a feasible approach to primary and secondary prevention of cardiac arrest and fits into the paradigm of food as medicine to address oxidative stress at its root.